Implementation of Student Effectiveness Using Project Based Learning (PJBL) Learning Model to Improve Learning Outcomes in Class X-ATU 1 Students at SMKN 1 Gondang - Dewi, Imega Syahlita; Purnomo, Denny Dwi (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2024)
This research was conducted with the aim of improving student learning outcomes using the Project Based Learning (PJBL) learning model in the subjects of Physics Science students at SMK Negeri 1 Gondang. This type of research uses the Classroom Action Research (PTK) method. The subjects are class X-ATU1 students at SMK Negeri 1 Gondang totaling 32 students. This research has a good impact on educational approaches that emphasize learning through real-world projects, where students are actively involved in exploration, collaboration, and problem solving. Real-world relevance and active student engagement are key focuses in PJBL, which encourages the development of critical thinking skills, creativity, and skills. This can be conveyed through the results of cycle I &; cycle II research, in cycle I with 22 students showing a percentage of 68% and carried out again in cycle II there was an increase in learning outcomes with 30 students showing a percentage of 82%. So in this study in cycles 1&2 experienced an increase in student learning outcomes.